REVOLUTIONIZING NIGERIAN HIGHER EDUCATION: ELECTRONIC RESOURCES AND ACADEMIC EMPOWERMENT - Adedipe , Nimbem Adebayo; Ogunlade , Afolabi Olufemi (Current Journal of Library and Information Sciences (CJLIS), 2023)
Electronic resources have emerged as indispensable tools for academic staff in Nigerian universities, enabling them to enhance their teaching, research, and overall productivity. These resources, encompassing e-books, online journals, e-data archives, and specialized databases like HINARI, AGORA, JSTOR, TEEAL, and Ebscohost, are accessed both on and off-campus. University libraries play a pivotal role in providing free access to these resources, greatly supporting academic research endeavors. This study examines the transformative impact of electronic resources on the research output of academic staff in Nigerian universities, shedding light on the pivotal role of these digital assets in knowledge creation and dissemination